The role of different parameters of synthesis in the final structure of Ti-containing mesoporous materials - Eimer, Griselda Alejandra (2008)
Ti-containing mesoporous materials have been prepared by hydrothermal synthesis at 373 K and compared to pure siliceous MCM-41 synthesized in the same conditions. A detailed and correlative study about the effect of different synthesis parameters on the physicochemical properties of the material has been carried out. All the samples showed typical XRD patterns of a kind MCM-41 structure. It seems that the synthesis time and the surfactant chain length are critical variables to obtain good structures. Mesoporous structure allowed the incorporation of different degrees of Ti loading, although a lower degree of ordering was observed with the increase of metal content above 1%. Moreover, a high incorporation of Ti into the structure seems responsible for the development of a secondary mesoporosity confirmed by TEM and associated with a pronounced hysteresis loop in the N2 isotherm. DRUVA-Vis and XPS studies revealed that the Ti species are mainly found isolated and tetrahedral coordinated into the framework. The superego-Ti(IV) species generated by the interaction of Ti-MCM-41 with aqueous H2O2 have been studied by EPR spectroscopy and correlated to DRUVA-Vis and XPS measurements.